PENGAWASAN PENGELOLAAN LIMBAH CAIR PADA INDUSTRI PENGOLAHAN KELAPA SAWIT DI KABUPATEN BANYUASIN (Study Empiris : Kecamatan Tanjung Lago) - Dian Kristiawan; Siti Zubaidah (JURNAL ILMIAH ILMU ADMINISTRASI, 2020)
This study discusses environmental monitoring which is an activity carried out directly or indirectly by the regional environmental supervisory apparatus to determine compliance with business and / or activity compliance with regulations in controlling environmental pollution. This research method uses qualitative research using the theory proposed by T. Hani Handoko (1995: 23) "Basic Oversight", namely: 1. Preliminary Supervision; 2. Supervision of Implementation; 3. Feedback Monitoring (After Implementation). Key informants were: Head of the Banyuasin District Environmental Agency, Head of Environmental Compliance and Capacity Building, Head of the Environmental Monitoring Section, Head of the Environmental Pollution Control Section, the Head of the Environmental Damage Control Section and the Company Management. The results of the research show that compliance with business and / or activities responsible for the regulation in controlling environmental pollution has problems, namely: the available budget is still limited for supervisory operational needs, the implementation of supervision in Banyuasin District seems slow and has not been implemented well apart from the lack of company compliance in reporting liquid waste management in Banyuasin Regency for that important role with stakeholders, namely the government, the community, and companies that produce waste is needed. Conducted joint supervision will have a very effective impact in overseeing industrial waste that will result in environmental pollution, while the company itself should periodically and continuously check the industrial waste produced